2010
DOI: 10.1200/jco.2009.25.1728
|View full text |Cite
|
Sign up to set email alerts
|

Do Radiation-Associated Soft Tissue Sarcomas Have the Same Prognosis As Sporadic Soft Tissue Sarcomas?

Abstract: PURPOSE To determine the prognostic significance of histologic type in radiation-associated soft tissue sarcomas (RASs) and determine whether RASs are associated with an inferior prognosis compared with sporadic soft tissue sarcomas (STSs). PATIENTS AND METHODS One hundred thirty primary RASs were identified from 7,649 STS patients from 1982 to 2007. Multivariate analysis of clinicopathologic factors for disease-specific survival (DSS) was performed for RASs, and a multivariate analysis of radiation exposure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
230
2
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(249 citation statements)
references
References 27 publications
11
230
2
6
Order By: Relevance
“…Although most radiation-associated sarcomas can be classified as undifferentiated pleomorphic sarcoma, angiosarcoma, or leiomyosarcoma, 25 3 tumor types with frequent alternative lengthening of telomeres, only 3 of the 15 radiation-associated sarcomas were alternative lengthening of telomeres positive (20%), and none was ATRX deficient.…”
Section: Alternative Lengthening Of Telomeres and Loss Of Atrx Expresmentioning
confidence: 99%
“…Although most radiation-associated sarcomas can be classified as undifferentiated pleomorphic sarcoma, angiosarcoma, or leiomyosarcoma, 25 3 tumor types with frequent alternative lengthening of telomeres, only 3 of the 15 radiation-associated sarcomas were alternative lengthening of telomeres positive (20%), and none was ATRX deficient.…”
Section: Alternative Lengthening Of Telomeres and Loss Of Atrx Expresmentioning
confidence: 99%
“…The prognosis for patients with RAS is poor and is comparable to the prognosis for patients with sporadic soft tissue sarcoma according to most authors, although Gladdy et al reported a worse prognosis for 130 patients who had RAS compared with their entire cohort of >7000 patients who had sporadic soft tissue sarcomas. 3,4,8 This may be because of a higher rate of incomplete resections caused by multifocal disease and the less frequent use of adjuvant radiotherapy for patients with RAS in their series. 8 The median latency period ranges from 59 to 103 months in the literature, which is in line with our data.…”
Section: Discussionmentioning
confidence: 99%
“…Радиоиндуцированные саркомы мягких тканей со-ставляют 0,45-2,5% от общего числа впервые диагно-стированных сарком мягких тканей [1][2][3]. Наиболее информативные данные были представлены Memorial Sloan-Kettering Cancer Center (2010), согласно которым за период с 1982 по 2007 г. среди 7649 наблюдений сарком мягких тканей, зарегистрированных в центре, лишь 130 (1,6%) являлись радиоиндуцированными [2].…”
unclassified
“…Наиболее информативные данные были представлены Memorial Sloan-Kettering Cancer Center (2010), согласно которым за период с 1982 по 2007 г. среди 7649 наблюдений сарком мягких тканей, зарегистрированных в центре, лишь 130 (1,6%) являлись радиоиндуцированными [2].…”
unclassified
See 1 more Smart Citation